DEVELOPING DIGITAL CAPACITY OF CIVIL SERVANTS AND CITIZENS MEETING DIGITAL TRANSFORMATION REQUIREMENTS IN VIETNAM - Hang, Chu Thi Thuy; Nhan, Nguyen Thi Thanh; Toan, Vu Manh; Luong, Nguyen Van (Veredas do Direito, 2026)
Digital technology development and digital transformation are inevitable trends, which have a direct impact on social development management. For the state, the digital governance model is established when implementing digital transformation; Public affairs activities are deployed on digital platforms, moving from the real environment to the digital environment. Digital transformation has formed and developed a digital government aimed at serving the people, meeting people's requests more quickly, accurately and effectively; but also poses requirements on the digital capabilities of subjects participating in state governance - civil servants and citizens. This study builds a theoretical framework on digital transformation and digital capacity requirements of civil servants and citizens to meet the requirements of digital transformation in state administration. The theoretical model includes 02 scales/independent variables "Developing digital capacity of civil servants" (CCS), "Developing digital capacity of citizens" (CCZ) and 01 scale/dependent variable "Digital transformation" (DTS). The author surveyed the opinions of 450 commune-level local government leaders of 3 provinces, including Quang Ninh province (Northern region), Quang Tri province (Central region), Vinh Long province (Southern region). The survey aimed to collect empirical information about the digital capacity of civil servants, the digital capacity of the people and the level of impact on digital transformation goals in state governance. From the conclusion of this empirical research, the author implies the issue of digital human resource development policy in Vietnam.